GP.04 Prevalence and determinants of seizure action plans in a pediatric epilepsy population. (5th June 2019) - Chiu, M; Peinhof, S; Borhani, M; DeGuzman, C; Siu, C; Kuzeljevic, B; Schrader, D; Huh, L; Connolly, MB
Abstract : Background: Status epilepticus (SE) is the most common pediatric neurological emergency. Timely treatment is crucial, yet administration of rescue medications is often delayed and under-dosed. We aim to improve SE management by ensuring that every child at risk of SE in our province has an individualized seizure action plan (SAP) outlining the steps that should be taken during SE.Methods: A survey was distributed to parents of epilepsy patients aged 1 month to 19 years. Primary outcome was percentage of patients with SAPs. Secondary outcome was parental interest in a SAP mobile application. Following chart review, univariate and multivariate analysis was performed to identify variables that predict whether patients have SAPs.Results: Of 192 participants, 61.5% have SAPs. On univariate analysis, history of prior SE and male gender increased likelihood of having a SAP. On logistic regression, Nagelkerke R2 was 0.204 and our model correctly predicted 82.2% of patients with SAPs. 83.3% of parents were interested in a SAP mobile application.Conclusions: This is one of the first studies to examine SAP prevalence in a pediatric epilepsy population. There is a need to increase the percentage of epilepsy patients with SAPs. Most parents would find a SAP mobile application valuable in their child's management.